2010
DOI: 10.1016/j.ydbio.2010.02.025
|View full text |Cite|
|
Sign up to set email alerts
|

CACN-1/Cactin interacts genetically with MIG-2 GTPase signaling to control distal tip cell migration in C. elegans

Abstract: The two specialized C. elegans distal tip cells (DTCs) provide an in vivo model system for the study of developmentally regulated cell migration. We identified cacn-1/cactin, a well-conserved, novel regulator of cell migration in a genome-wide RNAi screen for regulators of DTC migration. RNAi depletion experiments and analysis of the hypomorphic allele cacn-1(tm3126) indicate that CACN-1 is required during DTC migration for proper pathfinding and for cessation of DTC migration at the end of larval morphogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…It has been reported that [31][32][33]28]. Human Cactin has been reported to interact with IκBL, which is one of negative regulators of the NFκB signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that [31][32][33]28]. Human Cactin has been reported to interact with IκBL, which is one of negative regulators of the NFκB signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Human cactin was later found to physically and functionally interact with IκB-like protein (IκBL) and to be part of a negative feedback loop that controls NFκB transcriptional response (Suzuki et al, 2016), suggesting a conserved function for cactins in immune response and development (Atzei et al, 2010a). To date, cactin orthologs have been studied also in Toxoplasma gondii, Litopenaeus vannamei, Arabidopsis thaliana, Caenorhabditis elegans, and Danio rerio (Atzei et al, 2010b;Baldwin et al, 2013;Cecchetelli et al, 2016;Doherty et al, 2014;LaBonty et al, 2014;Szatanek et al, 2012;Tannoury et al, 2010;Zhang et al, 2014). In these organisms, cactin loss-of-function is associated with compromised cell viability and proliferation, and with developmental defects, highlighting the essentiality of cactin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CCDC-55, a coiled-coil containing protein of unknown function found in an operon with rnf-121 and rnf-5 , two E3 ubiquitin ligases, CACN-1, another coiled-coiled containing protein, homologous to the IKB/cactus binding protein CACTIN, and MIG-39, a nuclear BED finger domain protein have all been found to be necessary for proper cessation of DTC migration (9, 6365). Depletion of these genes via RNAi or by mutation results in gonad arms that migrate far past the vulva on the dorsal surface (Figure 4B).…”
Section: The Dtc Stops Migrating At a Specific Place And Timementioning
confidence: 99%
“…Often, the DTCs only stop migrating when unable to squeeze past the pharynx, or upon reaching the posterior end of the animal (65). Although the mechanism is not fully understood, CACN-1 and its homologs are emerging as regulators of splicing and/or post-transcriptional gene expression.…”
Section: The Dtc Stops Migrating At a Specific Place And Timementioning
confidence: 99%